Case Report : Suspected Sexual Intercourse Involving A 9 Years Old Child: Septia Eva Lusina, Putu Ika Widyasari, Haikal Nirfandi, M Nabil Sulthoni Eralsyah, Rangga Sakti Budi Putra, Sulthan Alam Yasyfa, Syafira Alifia Audiani - Widyasari, Putu Ika; Lusina, Septia Eva (Fakultas Kedokteran, 2025)
Sexual intercourse involving a child is a serious issue that can have detrimental effects on the physical, psychological, and social well-being of victims. One of the commonly used forensic evaluation methods is the examination of the genitalia to assess indications of penetration. However, this examination has limitations, as not all cases of suspected sexual intercourse leave clear physical signs. This case report discusses the forensic examination of a 9-year-old girl suspected of experiencing sexual intercourse. The examination results revealed abrasions and tear on the genitalia. Based on these findings, genital examination can serve as part of forensic evidence in proving cases of sexual violence. A more comprehensive approach, including a thorough clinical examination and forensic interview, is essential to ensure the accuracy of diagnoses in a case of suspected sexual intercourse involving a child. Keywords: suspected sexual intercourse involving a child, genitalia, forensic, visum et repertum